(untitled) (Semiárida, 2020)
Two groups of barrows of a genetically improved herd (A) and another one of a non improved (B), were controlled. The purpose of this work was to evaluate the carcass yield through the parameters: percentage (%) of lean tissue, backfat thickness and dressing percentage. Also, was to assess the association between the dressing percentage with the lean tissue percentage and backfat thickness in the improved groups. Barrows were fed from 50 kg live weight (l.W.) to slaughter 102 kg l.W., during 70 days into concrete housing in four groups of 3) pigs each. AII groups were fed ad-Iibitum with 14% crude protein (C.P.), 3.100 Kcal. digestible energy at kilogram (DElkg); 0.75% Ca; 0.50% P and 0.83% Iisine. The average results showed slgnlficant differences between treatments on measured parameters. Dressing percentage (p<0.05) A= 76,33 ± 3,00, B= 78,47 ± 3,32. Lean tissue percentage (p<0.01) A= 48,00 ± 2,61; B= 41,00 ± 2,41. Backfat results showed significant differences between treatments on measured parameters. Dressing percentage (p<0.05) A= 76,33 ± 3,60, B= 78,47 ± 3,32. Lean tissue percentage (p<0.01) A= 48,60 ± 2,61; B= 41,90 ± 2,41. Backfat thickness In mm (p<0.01) A= 15,89 ± 2,80; B= 23,76 ± 3,76. The simple lineal and quadratic regressions of the lean tissue percentage (r= 0.037 and r= 0.13) and backfal thickness lo the carcass yield were non significant (r= 0.105 and r= 0.106) respectively. 11 is important to emphasize the structural composition of the carcass of genetically improved herds. This gives the possibility to reach a belter price and also to improve the productive efficiency.